Multi-Pass Free Electron Laser Assisted Spectral and Imaging Applications in the Terahertz/Far-IR Range Using the Future Superconducting Electron Source BriXSinO - Koral, Can; Mazaheri, Zahra; Papari, Gian Paolo; Andreone, Antonello; Drebot, Illya; Giove, Dario; Masullo, Maria Rosaria; Mettivier, Giovanni; Opromolla, Michele; Paparo, Domenico; Passarelli, Andrea; Petrillo, Vittoria; et al. (Frontiers in Physics, 2022)
Free-Electron Lasers area rapidly growing field for advanced science and applications, and worldwide facilities for intense field generation, characterization and usage are becoming increasingly popular due to their peculiarities, including extremely bright, coherent, wide band tunable ultra-short pulses which are not achievable with other techniques up to now. In this review we give a thorough survey of the latest advances in the Free-Electron Laser-based field generation and detection methodologies and then present the main characteristics of a future THz/FIR source, named TerRa@BriXinO, based on a superconducting linear accelerator. The foreseen source is strongly monochromatic, with a bandwidth of 1% or smaller, highly coherent both transversally and longitudinally, with extreme versatility and high frequency tunability. After introducing the most recent and novel FEL-assisted scientific investigations, including fundamental explorations into complex systems and time-dependent interactions and material dynamics, we present our vision on the potential use of the TerRa facility and analyze some possible applications, ranging from non-linear physics under extreme conditions to polarization sensitive imaging and metamaterial-based sensing.